Old MacDonald had a farm - Illustrated by Mantle, Ben (London Usborne, 2010)
Join Old MacDonald on a day at the farm as he looks after his animals. Part of the Usborne Young Reading Program, aimed at children who are beginning to read
Include Color Illustration
Keywords: Domestic animals -- Farms